Desire for a child among HIV-infected women receiving antiretroviral therapy in Cameroon: results from the national survey EVAL (ANRS 12-116) - (:unkn) unknown (My University, 2010)
The majority of HIV-infected people in sub-Saharan Africa are women, many of reproductive age. Cameroon is severely hit by the AIDS epidemic and has developed a large national program for improving access to antiretroviral treatment (ART). The reproductive intentions of women living with HIV/AIDS (WLHA) who obtain access to ART in this country remain poorly documented. Our study aimed at exploring factors associated with the desire to have a child among 1,433 ART-treated fertile WLHA aged <50. Analyses were based on data collected during the national cross-sectional survey EVAL (ANRS 12-116), which was conducted between September 2006 and March 2007 in 27 HIV care centers in Cameroon. Logistic regression was used to explore factors associated with women's desire to have a child, defined as reporting the wish to have a/another child. A total of 791 women (55%) reported the desire to have a child. After adjusting for age, matrimonial status, number of biological children and sexual activity, the main factors independently associated with this desire in a multivariate analysis were having a good physical health-related quality of life (HRQL) (1.02[1.01-1.03] for a one-point increment on the SF-12 scale) and a CD4 count at ART initiation <200 cells/mm3 (1.7[1.2-2.4]). As a conclusion, the desire to have a child is frequent among ART-treated WLHA in Cameroon. HIV care and family planning programs should be integrated more thoroughly in order to support WLHA's reproductive choices.
Keywords: African Research